Pemanfaatan Tempurung Kelapa sebagai Katalis pada Proses Konversi Minyak Curah Menjadi Biodiesel - Yustia Wulandari Mirzayanti; Erlinda Ningsih; Zain Lillahulhaq; Zuhdi Ma’sum; Chevy Renova; Yasin Wijaya (2477 - 6165, 2020)
Vegetable oil is one of the alternative sources of raw material for fuel oil to produce biodiesel. The conversion reaction process requires the help of a catalyst to break down triglycerides into methyl esters. Therefore, this study aims to determine the performance of catalysts made from coconut shells to convert bulk oil into biodiesel. The catalyst performance is focused on biodiesel's yield parameters through the influence factor of catalyst weight, molar ratio, and %FAME. This research was conducted in three stages, namely (1) catalyst preparation, (2) application of catalyst performance through the conversion process of bulk oil into biodiesel, (3) washing of biodiesel. The first stage was catalyst preparation carried out by utilizing a coconut shell, which was first made into charcoal, then activated using H3PO4 then sulfonated with H2SO4. The second stage was the conversion process of bulk oil into biodiesel using coconut shell catalysts through a transesterification process using variations in the catalyst's weight to bulk oil (0.5; 1; 1.5; 2; and 2.5% wt/wt) and bulk oil molar:methanol ratio (1: 3; 1: 6; and 1: 9). The third stage was the process of washing biodiesel using HCl. Based on this study's results, the best catalyst weight was 2% wt/wt with a molar ratio of 1: 9 resulting in the highest yield of 89% and the FAME of 80.36%.